Occurrence and clonal diversity of multidrug-resistant Klebsiella pneumoniae recovered from inanimate surfaces in Algerian hospital environment: First report of armA, qnrB and aac(6′)-Ib-cr genes. (September 2017) - Zenati, Karima; Sahli, Farida; Garcia, Vincent; Bakour, Sofiane; Belhadi, Djellali; Rolain, Jean Marc; Touati, Abdelaziz
Highlights: High prevalence of MDR K. pneumoniae isolates from the inanimate surface in Algeria. First report of armA, qnrB and aac(6′)-Ib-cr genes in the hospital environment in Algeria. Dissemination of MDR clones in the hospital environment. First study that investigated the clonal diversity in MDR environmental K. pneumoniae . Exceptional adaptation to the environment can contribute to the difficulty in restricting the spread. Abstract: Purpose: The aim of this study is to characterize the molecular support of antibiotic resistance in MDR K lebsiella pneumoniae recovered from inanimate surfaces between March 2012 to February 2014 in three teaching hospitals (Setif, Bejaia and Constantine) in Algeria. Results: Forty-four K. pneumoniae producing ESBL were detected and bla CTX-M-15 and bla CTX-M-3 were detected respectively in 41 and 3 isolates. These K. pneumoniae isolates producing ESBL were also resistant to gentamicin (87%), tobramicin (87%), ciprofloxacin (66%) and ofloxacin (62%). Aminoglycosides resistance genes detected were 16S rRNA methylase ( armA ), aminoglycoside acetyl-transferase ( aac(6′)-Ib ), aminoglycoside nucleotidyl-transferase ( aadA2 ) and aminoglycoside, phosphoryl-transferase ( ant3″Ih-aac(6′)-IId ). Plasmid-mediated quinolone resistance (PMQR) genes detected were aac(6′)-Ib -cr (34 isolates) and qnrB genes in (34 isolates). Multilocus sequence typing (MLST) resulted in 12 different sequence types (STs) regrouped into 5 clonal complexes (CC147, CC17, CC37, CC2 and CC23), one clonal group (CG485) and 4 singletons (ST1426, ST405, ST1308, ST873). Conclusion: Here, we report the detection of the ESBLs encoding gene linked with plasmid-mediated quinolone resistance (PMQR) and aminoglycosides resistance recovered from inanimate surfaces in hospital environment.